Hydrographic datum planes - Marmer, Harry A. (The International Hydrographic Review, 2025)
This manuscript is a reprint of the original paper previously published in 1929 in the Hydrographic Review, a predecessor journal of The International Hydrographic Review (IHR, https://ihr.iho.int/): Marmer, H. A. (1929). Hydrographic datum planes. Hydrographic Review, 6 (1), 37–51. https://journals.lib.unb.ca/index.php/ihr/article/view/28153